An Information Service by Using a Scientific Approach for Preventing Student Cyberbullying - Syarifuddin Syarifuddin; A. Muri Yusuf; Neviyarni Neviyarni; Netrawati Netrawati (Global Econedu, 2020)
Cyber-bullying is a massive phenomenon happened to students. Student cyber-bullying must be prevented because it can give a negative physical and psychological impact on the offender, audience and victim. One way that can be done to prevent student cyber-bullying is to provide an information service by using a scientific approach. The purpose of this research was to examine the effectiveness of an information service by using a scientific approach to prevent student cyber-bullying. The research method used was a quantitative research with the true experiment design pretest-posttest group design. The research sample consisted of 30 students for the experimental group and 30 students for the control group taken by using a proportional stratified random sampling technique. The data were analyzed by using the descriptive statistical analysis and non-parameteric statistics using the Kolmogorov Smirnov 2 Independent Sample analysis technique. The results of this research prove that the information service by using a scientific approach is effective in preventing student cyber-bullying.